2018
DOI: 10.34035/jk.v9i2.287
|View full text |Cite
|
Sign up to set email alerts
|

Art Drawing Therapy Efektif Menurunkan Gejala Negatif Dan Positif Pasien Skizofrenia

Abstract: ABSTRAK Skizofrenia adalah gangguan jiwa yang ditandai dengan gangguan pikiran, bahasa, persepsi, dan sensasi mencakup pengalaman psikotik berupa gejala positif dan negatif. Penelitian ini bertujuan untuk mengetahui efektifitas art drawing therapy terhadap penurunan skor PANSS pasien skizofrenia di ruang Srikandi RSJD Dr. Arif Zainudin Surakarta. Penelitian ini menggunakan rancangan quasi experimen dengan pre test–post test with control group design. Jumlah sampel sebanyak 10 responden diambil dengan teknik pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Respondents were taken using purposive random sampling technique, the results showed that the value of p = 0.000 (<0.05), which means that art therapy drawing is effective in reducing negative and positive symptoms in schizophrenic patients. [7] This is because with drawing activities respondents can tell stories, express thoughts, feelings and emotions that are usually difficult to express, so that drawing activities can provide motivation, entertainment and joy which can reduce feelings of anxiety. Anger or emotional and corrects chaotic thoughts and increases motor activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Respondents were taken using purposive random sampling technique, the results showed that the value of p = 0.000 (<0.05), which means that art therapy drawing is effective in reducing negative and positive symptoms in schizophrenic patients. [7] This is because with drawing activities respondents can tell stories, express thoughts, feelings and emotions that are usually difficult to express, so that drawing activities can provide motivation, entertainment and joy which can reduce feelings of anxiety. Anger or emotional and corrects chaotic thoughts and increases motor activity.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria for search were studies conducted on patients with hallucinations, intervention with occupational drawing therapy, Indonesian language journals, free journals and full text with the outcome controlling for hallucinations. As much 3 journals [5] [6,7] that discuss occupational therapy drawing on changes in hallucinations. Occupational therapy, drawing activity on changes in hallucinations in schizophrenic patients with a sample size of 30 people, showed that the hallucination symptoms experienced by schizophrenic patients before being given occupational therapy, drawing the most activity in the moderate category, namely 15 people (50%), and after give okupais drawing therapy, the most data is in the light category, namely 21 people (70%).…”
Section: Equipmentmentioning
confidence: 99%
See 1 more Smart Citation